Internationales Archiv für Sozialgeschichte der deutschen Literatur (De Gruyter, 1976)
IASL explores the relationship between literary texts and socio-historical contexts, focusing on German literary history from the Middle Ages to the present. Main interests are the foundations of literary history in literary theory, especially where literary studies meets with history and the social sciences.